Zooplankton-phasmavirus population genetic and prevalence data in Subarctic ponds, 2011-2015 - Derek Taylor (Arctic Data Center, 2017)
The file contains sequence alignments (population data) of individual phantom midges from permanent ponds, (Chaoborus spp.) and their associated RNA viruses ( Orthophasmaviridae: Kigluaik phantom virus or KIGV, Nome phantom virus or NOMV). The host sequences are from two genes from the mitochondrial genome while the viral sequences are from all four genes in their respective genomes. To preserve annotations, the alignment data files are in the Sequin format (freely available from NCBI). All files are readily converted to the FASTA format within Sequin. Virus prevalence data are given for 25 ponds (and a five year window for one site). Also virus screening data (from reverse transcription PCR) for non-midge arctic zooplankters are given. Study ponds (co-ordinates are provided in a file ) are both recent thaw and glacial ponds on the Seward Peninsula, AK, and Baffin Island, Canada.